Numerical Study of Three-Dimensional Flow in a Negative Pressure Isolation Room with One Inlet and Two Outlets Ventilation Configurations with Variations in Bed Positions and Variations in Outlets Pressure Differences - Wawan Aries Widodo; Rifqi Amin Muhlis (JMES: The International Journal of Mechanical Engineering and Sciences, 2023)
Designing the negative pressure isolation room need good ventilation planning. The design of the ventilation system must make every part of the room well circulated so that the air does not stagnate. In addition, the air must not be short-circuited between the inlet and outlet. Aspects of the comfortability of the patient must be considered including temperature, velocity and air pressure in the room. By doing simulation, it is expected that the optimal flow characteristics can be known in order to maintain the air condition of the isolation room at a low infection level and the patient in the room still feels comfortable. The method used in this research is a three-dimensional numerical study in a negative pressure isolation room with a size of 6 m x 8 m x 3 m. Variations carried out in this study are position of the patient's bed and difference in the outlet pressure of -2.5Pa, -5 Pa, -8 Pa, -15 Pa, respectively. The boundary conditions at the inlet uses a mass flow inlet type with a mass rate at 0.5642 kg/s (12 ACH ) and at the outlets use a pressure outlet type. The results obtained from this study are that the outlet pressure variation of -5 Pa is the best variation because it can create a negative pressure room according to existing standards and also patient still fell comfort because the room pressure is not too negative. The configuration of the isolation room with one bed has better airflow characteristics than the isolation room with two beds because there is no air stagnation in the area above the bed. Patient comfort can be maintained because the speed in the bed area is less than 0.2 m/s, the temperature near the bed is less than 28 oC, and the room pressure does not reach -1mmHg or -133 Pa (Gauge Pressure).